The Potential of Rafting as A Sport Tourism in Randudongkal District Pemalang Regency Central Java - Kartiko, Islah Tri; Rahayu, Setya; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2023)
This research aims to analyze 1 the potential strengths of Rafting as a tourism sport in Randudongkal District, Pemalang Regency, Central Java, 2) Analyze the potential weaknesses of Rafting as a tourism sport in Randudongkal District, Pemalang Regency, Central Java, 3) Analyze the potential opportunities for Rafting as a tourism sport in Randudongkal District, Pemalang Regency, Central Java, 4) Analyzing the potential threat of rafting as a tourism sport in Randudongkal District, Pemalang Regency, Central Java. This type of research uses a descriptive qualitative approach using SWOT analysis. The subjects of this research were the Youth, Sports and Tourism Department of Pemalang Regency, Randudongkal District, Kecepit Village Government, Mejagong Village Government, Business Actors, Tourists and the Community in Kecepit-Mejagong Village, Randudongkal District. Through observation, interviews and documentation approaches, the validity of the data uses Triangulation, the data analysis model used in the research is data collection, data reduction, data presentation and drawing conclusions. The research results show that the potential of rafting as a tourism sport in Randudongkal District, Pemalang Regency, Central Java, based on the SWOT matrix, includes: 1) The sport of rafting has a uniqueness which is supported by its geographical location and the creativity of business owners, 2) A form of promotion that is less widespread only uses media platforms. social, 3) The government's performance in developing rafting sports by relying on Pokdarwis also to promote the Pemalang Regency area, 4) There is an impact on the social life of the community from rafting sports in Kecepit Village, such as changes in community professions and forms of competition among village communities.